Making a Tourism Icon: The valorization of Siti Nurbaya Bridge in West Sumatera - Endriani, Deni (Jurnal Master Pariwisata (JUMPA); Volume 01, Nomor 02, Januari 2015, 2015)
This article discusses about Siti Nurbaya Bridge in Padang, West Sumatera, which is considered to have potency to be expanded into a tourism icon. By being an attractive tourism object, this awesome place could give some benefits for local people as well as the government. This article is focused on the bridge and the visitors, the weaknesses and strenghts of the attraction, and how the weaknesses can be reduced to create a more attractive, enjoyable, and beneficial tourism object in Padang. The data was collected trough observations, interviews, and literary studies. It is found that there are two options offered in order to develop and valorize the tourism value of the bridge. They are creating a culinary night market and holding a traditional art performance called Randai.